2012
DOI: 10.1186/1471-2180-12-258
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory proteins contribute differentially to Campylobacter jejuni’s survival and in vitro interaction with hosts’ intestinal cells

Abstract: BackgroundThe genetic features that facilitate Campylobacter jejuni’s adaptation to a wide range of environments are not completely defined. However, whole genome expression studies showed that respiratory proteins (RPs) were differentially expressed under varying conditions and stresses, suggesting further unidentified roles for RPs in C. jejuni’s adaptation. Therefore, our objectives were to characterize the contributions of selected RPs to C. jejuni’s i- key survival phenotypes under different temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 42 publications
(70 reference statements)
2
41
0
Order By: Relevance
“…C. jejuni 81–176 (wildtype)24 was cultured on Mueller-Hinton (MH) agar at 42 °C under microaerobic conditions (85% N 2 , 10% CO 2 , 5% O 2 ) or under <1% O 2 (hereafter referred to as anaerobic conditions) which was generated using the BD GasPak Sachets system (BD Diagnostics, NJ, USA)11. The Campylobacter selective supplement (SR155E, Oxoid, KS, USA), sodium formate, sodium succinate, sodium fumarate, sodium cyanide, sodium azide and sodium nitrate (Sigma, MO, USA) were added to the MH medium when necessary.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…C. jejuni 81–176 (wildtype)24 was cultured on Mueller-Hinton (MH) agar at 42 °C under microaerobic conditions (85% N 2 , 10% CO 2 , 5% O 2 ) or under <1% O 2 (hereafter referred to as anaerobic conditions) which was generated using the BD GasPak Sachets system (BD Diagnostics, NJ, USA)11. The Campylobacter selective supplement (SR155E, Oxoid, KS, USA), sodium formate, sodium succinate, sodium fumarate, sodium cyanide, sodium azide and sodium nitrate (Sigma, MO, USA) were added to the MH medium when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of formate on motility and biofilm formation was determined as described previously1127. To evaluate motility, C. jejuni cultures were adjusted to OD 600 of 0.02.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These NiFe hydrogenases have been shown or predicted to enable a number of pathogens to use molecular H 2 within the host as a respiratory energy-yielding substrate (16)(17)(18)(19)(20)(21)(22)(23)(24). Previous studies in our laboratory have shown that each of the membrane-associated uptaketype respiratory hydrogenases contributes to the survival and growth of S. Typhimurium within the host.…”
mentioning
confidence: 99%